A Novel Stress-Diathesis Model to Predict Risk of Post-operative Delirium: Implications for Intra-operative Management - El-Gabalawy, Renée; Patel, Ronak; Kilborn, Kayla; Blaney, Caitlin; Hoban, Christopher; Ryner, Lawrence; Funk, Duane; Legaspi, Regina; Fisher, Joseph A.; Duffin, James; Mikulis, David J.; Mutch, W. Alan C. (Frontiers in Aging Neuroscience, 2017)
Risk assessment for post-operative delirium (POD) is poorly developed. Improved metrics could greatly facilitate perioperative care as costs associated with POD are staggering. In this preliminary study, we develop a novel stress diathesis model based on comprehensive pre-operative psychiatric and neuropsychological testing, a blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) carbon dioxide (CO2) stress test, and high fidelity measures of intraoperative parameters that may interact facilitating POD. Methods: The study was approved by the IRB at the University of Manitoba and registered at clinicaltrials.gov as NCT02126215. Twelve patients were studied. Pre-operative psychiatric symptom measures and neuropsychological testing preceded MRI featuring a BOLD MRI CO2 stress test whereby BOLD scans were conducted while exposing participants to a rigorously controlled CO2 stimulus. During surgery the patient had hemodynamics and end-tidal gases downloaded at 0.5 hz. Postoperatively, the presence of POD and POD severity was comprehensively assessed using the Confusion Assessment Measure –Severity (CAM-S) scoring instrument on days 0 (surgery) through post-operative day 5, and patients were followed up at least 1 month post-operatively. Results: Six of 12 patients had no evidence of POD (non-POD). Three patients had POD and 3 had clinically significant confusional states (referred as subthreshold POD; ST-POD) (score ≥ 5/19 on the CAM-S). Average severity for delirium was 1.3 in the non-POD group, 3.2 in ST-POD, and 6.1 in POD (F-statistic=15.4, p < 0.001). Depressive symptoms, and cognitive measures of semantic fluency and executive functioning/processing speed were significantly associated with POD. Second level analysis revealed an increased inverse BOLD responsiveness to CO2 pre-operatively in ST-POD and marked increase in the POD groups when compared to the non-POD group. An association was also noted for the patient population to manifest leucoaraiosis as assessed with advanced neuroimaging techniques. Results provide preliminary support for the interacting diatheses (vulnerabilities) and intraoperative stressors on the POD phenotype. Conclusions: The stress-diathesis model has the potential to aid in risk assessment for POD. Based on these initial findings, we make some recommendations for intraoperative management for patients at risk of POD.